2013
DOI: 10.1016/j.mimet.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and reliable MALDI-TOF mass spectrometry identification of Candida non-albicans isolates from bloodstream infections

Abstract: Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) fingerprinting has recently become an effective instrument for rapid microbiological diagnostics and in particular for identification of micro-organisms directly in a positive blood culture. The aim of the study was to evaluate a collection of 82 stored yeast isolates from bloodstream infection, by MALDI-TOF MS; 21 isolates were identified also directly from positive blood cultures and in the presence of other co-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 29 publications
0
37
1
5
Order By: Relevance
“…Este nuevo recurso permite la correcta identificación de especie superando a Vitek II 17 , y aún es posible esperar mayores beneficios si se usa directamente la sangre de la botella del frasco de hemocultivo logrando identificación en 30 min; con ello se alcanza una concordancia con los métodos tradicionales de 96% para C. albicans y 86% para C. no-albicans 17,18 .…”
Section: Discussionunclassified
“…Este nuevo recurso permite la correcta identificación de especie superando a Vitek II 17 , y aún es posible esperar mayores beneficios si se usa directamente la sangre de la botella del frasco de hemocultivo logrando identificación en 30 min; con ello se alcanza una concordancia con los métodos tradicionales de 96% para C. albicans y 86% para C. no-albicans 17,18 .…”
Section: Discussionunclassified
“…The use of matrixassisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for the rapid identification of clinical yeast and mycobacterial isolates has been evaluated in some studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, there has been a limited number of direct comparison studies focusing on the performance of the two MALDI-TOF systems to rapidly identify yeast and mycobacterial clinical isolates (26)(27)(28).…”
mentioning
confidence: 99%
“…In their study, Lavergne (2013) and Marinach-Patrice (2010) used the same protocol as ours and were able to rapidly and precisely identify the main Candida species, thus avoiding the need for culture on a specific medium. In a second study carried out by Pulcrano et al (2013), on Candida non-albicans with 0.5% SDS, all 82 strains were identified at the species level with a score greater than 2.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, only one genus of yeast, Candida, was isolated unlike Yan et al (2011), who found yeasts belonging to two genera: Candida and Cryptococcus. Pulcrano et al (2013) identified yeasts of the genera Saccharomyces and Lodderomyces in addition to the genus Candida.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation